PENGARUH METODE KARYAWISATA (FIELD TRIP) TERHADAP KEMAMPUAN MENULIS TEKS PUISI PADA SISWA KELAS X SMK NEGERI 2 KARAWANG TAHUN AJARAN 2017/2018 - Devy Permatasari; Wikanengsih Wikanengsih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims to explain the influence of field trip method in learning to write poetry text on class X student of Administration Office 2 SMK Negeri 2 Karawang. The population in this study is all students of class X Administration Office 2 SMK Negeri 2 Karawang with the number of 50 students. The sample in this study amounted to 25 students taken at random simple with random sampling. The instrument used to collect data is the assignment of essay writing essay writing poetry. The method used in this research is the experimental method. Hypothesis testing is done by using "t" test of data processing, obtained the average value of pre test (pre-test) 9,6 and end test (post-test) 14,2. T-count is 2,760 and df 72, p value is obtained 0,002 so p <0,05 meaning significant. So that there is a difference in this study and based on statistical calculations obtained means that the final test (post-test) is better than pre-test and field trip method is very effective to be used in learning to write poetry text.